(untitled) (Bangladesh Medical Journal, 2026)
“Urine-like diarrhea” is classically described in congenital chloride-losing diarrhea (CCLD), a rare neonatal-onset secretory diarrheal disorder. Presentation of similar stool characteristics in older children without CCLD is extremely uncommon. A 10-year-old Bangladeshi girl presented with 15 days of frequent passage of clear, watery stool described by her mother as “urine-like,” occasionally mixed with mucus. There was mild pre-defecation abdominal cramping but no fever, blood in stool, tenesmus, or weight loss. Physical examination was largely unremarkable except for an ill-defined mobile mass in the right iliac fossa. Laboratory investigations, including complete blood count, inflammatory markers, serum electrolytes, thyroid profile, HIV screening, and celiac serology, were normal. Stool examination, culture, and Clostridium difficile toxin assay were negative. Stool electrolytes showed low sodium, potassium, and chloride levels, with a low stool osmolality and low osmotic gap suggestive of secretory diarrhea. Endoscopy, colonoscopy, abdominal CT, and tumor markers (calcitonin, gastrin) were normal. However, a plain abdominal X-ray revealed fecal impaction in the right colon. During bowel preparation with polyethylene glycol and sodium phosphate enema, a large amount of fecal matter was expelled, followed by complete resolution of diarrhea.Colonic fecal impaction can present atypically as persistent “urine-like” watery diarrhea in older children. Recognition of this presentation can prevent unnecessary invasive investigations and lead to prompt, effective treatment. Bangladesh Med J. 2025 Sept; 54(1): 39-43